Sustainable Energy in Aviation with Reverse FMEA Analyses - Menyhárt, József; Al-Aghbari, N. G. E. (International Journal of Engineering and Management Sciences, 2024)
This research aims to identify and evaluate the key challenges and obstacles hindering the adoption of sustainable energy in the aviation industry. The outcomes and insights derived from this research will be synthesized to provide a comprehensive overview of the opportunities and suggestions for the adoption of sustainable energy in the aviation industry. The objective of this study is to help the aviation industry’s shift toward more sustainable energy sources in order to reduce its environmental footprint and mitigate the effects of climate change.